UPAYA MENINGKATKAN EKONOMI PEDESAAN MELALUI DANA DESA DI DESA REJOSARI MATARAM LAMPUNG TENGAH - Pujianto, Erik (Jurnal Signaling, 2025)
Decentralization has been Indonesia's chosen concept for implementing government programs for approximately 27 years. Villages are now autonomous regions and given full authority to manage their own governance. This autonomy began with the introduction of village funds in 2015. This initiative aimed to boost development in rural areas. However, most villages and village governments lack the capacity to manage village funds. This research employed qualitative methods, including interviews, observation, and documentation to obtain the desired results. To obtain valid information, the researcher used the Rejosari Mataram Village Head as the primary source. The results indicate that the Rejosari Mataram Village Government lacks sufficient capacity to manage village funds optimally. This is evident in the lack of sustainable, innovative programs that could potentially boost the village community's economic growth. A comparison of Ministerial Regulation No. 7 of 2023 with the actual use of village funds in Rejosari Mataram Village in 2024 reveals a gap between the priorities mandated by the regulation and the achievements of implementation on the ground. The suggestion that researchers can give is that the Rejosari Mataram village government must be more innovative in designing programs for using Village Funds.